O dever de divulgação de informação privilegiada - Antunes, José Engrácia (2020)
Issuers who have requested or approved admission of their financial instruments to trading on a Regulated Market must inform the public as soon as possible of any inside information relating directly to them, that is, information that is non-public, precise, and if it were made public would be likely to have a significant effect on the price of the issuer’s financial instrument or related financial instruments. This paper aims at describing and analysing the concept and regulation of this duty of disclosure of inside information under Portuguese law